Pemanfaatan Media Sosial Instagram oleh Redaksi Kuninganmass - Stefani Wijaya; Aryo Subarkah Eddyono (Expose: Jurnal Ilmu Komunikasi, 2021)
Currently, various media use social media with various motivations. One of the media that does this is a local online media in Kuningan, West Java, namely Kuninganmass. Kuninganmass chose Instagram because it has many features that can be used for editorial purposes. Kuninganmass Instagram has 25.2 thousand followers and has superior interaction compared to other local online media such as Radar Kuningan, Kuningan Dialectics, FrameWarta, SuaraKuningan, Ciremai Today, Kuninganmedia. This research answers: how does Kuninganmass utilize Instagram? The research method used is qualitative. Data were collected through interviews, observations and documents. The results of this study are that the Kuninganmass editor uses Instagram for the purposes of news distribution, news gathering, content promotion and sales as well as new interaction media. Kuninganmass utilizes Instagram social media by using Instagram features such as Instagram stories, Instagram TV, Instagram live, uploading content, and direct messages. Kuninganmass' motivation to use Instagram is to find out the effect of using Instagram social media on readers, introduce the name Kuninganmass and expand segmentation, especially reaching the segmentation of young people. With the use of Instagram, Kuninganmass has succeeded in increasing the youth segment, introducing the name Kuninganmass more broadly and getting additional alternative income. Suggestions for further research is to see how newsrooms are affected by social media culture in producing their content.